Protective effect of vaccination against mumps complications, Czech Republic, 2007-2012 - Hana Orlíková; Marek Malý; Pavla Lexová; Helena Šebestová; Radomíra Limberková; Lucie Jurzykowská; Jan Kynčl (BMC, 2016)
Abstract Background In the Czech Republic, two-dose immunization against mumps achieves 98 % coverage. The routine reporting detects mumps cases, clinical complications, and hospital admissions in unvaccinated but also in vaccinated individuals. Using surveillance data of patients with mumps we assessed the effectiveness of mumps vaccination on mumps clinical complications and hospitalization need. We also investigated the effect of the time since immunization. Methods We analysed data on incident mumps cases reported to the Czech national surveillance system in 2007-2012. Using a logistic regression model with adjustment for age, sex, year of onset, and the administrative region, the association between vaccination and the most frequent mumps complications and hospitalization was evaluated. The adjusted odds ratios (ORa) for mumps complications were compared between the vaccinated and non-vaccinated groups, reflecting the vaccine effectiveness (VEa) computed as VEa = (1-ORa)×100. We estimated the risk of mumps complications by the time from vaccination. Results From total of 9663 mumps analysed cases 5600 (58 %) occurred in males. The mean age at the disease onset was 17.3, median 16 years. Ninety percent of the study patients had no complications, while 1.6 % developed meningitis, 0.2 % encephalitis, and 0.6 % pancreatitis. Mumps orchitis occurred in 659 (11.8 %) male cases. In total, 1192 (12.3 %) patients required hospitalization. Two doses of vaccine received by 81.8 % cases significantly reduced the risk of hospitalization: ORa 0.29 (95 % CI: 0.24, 0.35). Two doses showed statistically significant VEa 64 % (95 % CI: 46, 79) for meningitis, 93 % (95 % CI: 66, 98) for encephalitis in all cases, and 72 % (95 % CI: 64, 78) for orchitis in males. Vaccine effectiveness for orchitis declined from 81 to 74 % and 56 % in the most affected age groups 10-14, 15-19, and 20-24 years, respectively. Among 7850 two-dose recipients, the rate of complications rose from below 1 to 16 % in categories up to 6 years and 24 and more years after the second dose, respectively. Conclusions This study demonstrates a significant preventive effect of two-dose vaccination against mumps complications (orchitis, meningitis, or encephalitis) and hospitalization for mumps. The risk of complications increases with time interval from vaccination. Teenagers and young adults were the most affected age groups.